Common fixed-point theorems for non-linear non-self contractive mappings in convex metric spaces - Kumar Santosh; Aron David (Topological Algebra and its Applications, 2023)
In this article, two pairs of non-self mappings satisfying a collection of non-linear contractive conditions in convex metric space are considered to prove a common fixed-point theorem. An appropriate example is provided to support the results proved herein. In addition, we have proved a theorem as an application of our main result. Our results generalize and extend several existing theorems in the literature.